Eco‐physiological and morphological traits explain alpine plant species' response to warming. (18th November 2022) - Visakorpi, Kristiina; Block, Sebastián; Pellissier, Loïc; Levine, Jonathan M.; Alexander, Jake
Abstract: Understanding the traits mediating species' responses to climate change is a cornerstone for predicting future community composition and ecosystem function. Although species' eco‐physiological properties determine their response to environmental change, most trait‐based studies focus on a small subset of easily measured morphological traits as proxies for physiology. This choice may limit our ability to predict the impacts of climate change on species' demography, and obscure the underlying mechanisms. We conducted a transplantation experiment along a 1000‐m elevation gradient in the Alps to quantify the degree to which changes in plant abundance due to climate warming were predicted by eco‐physiological performance versus common morphological traits. Physiological measurements revealed that warming favoured species with a conservative leaf‐level water use strategy whereas species whose leaf‐level water use was more 'wasteful' were more likely to suffer from the warmer and drier climate. Nevertheless, the predictive power of physiological traits did not exceed that of morphological traits. Our results, therefore, show that while easily measured morphological traits can successfully predict plant abundance responses to climate, eco‐physiological approaches are needed to understand the underlying mechanism. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.